The Effectiveness of Counseling on Mothers' Typhoid Prevention Knowledge among Pediatrics’ Inpatients: The Effectiveness of Counsling on Mother’s Typhoid Prevention Knowledge Among Pediatrics’ Inpatients - Adhi Permana; Rika Agustina; Putri Amaliah Badri; Thia Prameswarie; Ahmad Ghiffari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Worldwide, typhoid disease affects between 11 and 20 million individuals annually. The risk is higher for men, for those with less education, and for those less than fourteen years old. This study aims to examine the impact of counseling on typhoid prevention knowledge among patients at Muhammadiyah Hospital. A pre-experimental one-group pretest-posttest approach was employed to interview 30 participants to evaluate their knowledge levels prior to and following counseling. The Marginal Homogeneity Test indicated a rise in average knowledge levels from 2.03 to 2.80. The findings indicated that counseling enhances understanding of typhoid prevention, underscoring the necessity of basic healthcare education for patients and their families.